A STUDY OF THE DIGITAL TRADE IN THE UNITED KINGDOM IN THE CONTEXT OF ADAPTATION TO THE UKRAINIAN MARKET - SHEVCHENKO, Iryna; ZVARYCH, Iryna; KRAVCHUK, Denys (Journal of European Economy, 2023)
The paper investigates aspects of digital trade in the United Kingdom and the possibility of adopting this experience in Ukraine. The authors analyse the performance of digital trade by segment and identify three clusters based on which they construct a mechanism for introducing the U.K. experience into the development of digital trade in Ukraine. By means of indicator systematization, the authors track the dynamics of gross value added in the sectors of IT, software and computer services, computer programming, consulting, and software publishing. The work identifies the tech companies based on the data of London Stock Exchange. Based on the analysis of average earnings in the U.K. digital sector by age group, the authors substantiate their suggestions aimed at creating new jobs for all age groups in Ukraine. Graphics illustrate the dynamics and trends of GDP growth from investment into digital technology in the United Kingdom over the period from 2020 to 2040. Based on this, the authors delineate the factors of influence and design the mechanism of introducing the U.K. experience into the development of digital trade in Ukraine. JEL: F50, O30, O52, Q01.